THE REFORMATION AS A RETURN TO THE GOD OF REVELATION: The Indian Significance of Martin Luther - Subhash Anand (Asian Horizons, 2017)
If the ecumenical movement as the common search towards the visible unity of Christians is to bear fruit, we need to rediscover how we receive God’s self-disclosure. The present article first examines how Luther understands ‘revelation.’ Then the author discusses the role of creation and history — not merely of Abraham and his descendants — as channels of divine self-disclosure. Jesus is presented as the revelation, and consequently as the hermeneutic key to understand the revelatory character of creation and history. If creation, history and Jesus mediate revelation, then we need to safeguard creation; ensure that humans who shape history, are governed by values; and return to Jesus by a thorough use of the historic-critical method.